The use of performance-enhancing drugs among athletes in some ancient and modern cultures: past and present - Mohammed Ali Al-Awdi, Fouad (sports creativity, 2025)
The aim of this study was to identify doping in some peoples in ancient times and modern, as well as to identify the most important reasons that led to the abuse of doping in ancient times and modern, the researcher used the experimental method because it is adequate for this study. The researcher used the experimental method because it is adequate for this study. The results of this study that the ancient civilizations used Doping to increase physical efficiency and increase muscle strength and to overcome the environmental conditions and to overcome the competitors in the Olympic Games and sporting the old And also there were differences in the reasons that led them to the use of Doping among the people of ancient and modern. The pursuit of fame and money is a cause of doping in athletes in the modern times.